2019
DOI: 10.1007/s00268-019-05101-z
|View full text |Cite
|
Sign up to set email alerts
|

Unfinished Business: A Systematic Review of Stump Appendicitis

Abstract: Background Stump appendicitis is defined as interval inflammation of any residual appendicular tissue, after an appendicectomy. We present a systematic review of case series and case reports on stump appendicitis, emphasising on risk factors, diagnosis and surgical management. Methods The English literature (1945–2018) was reviewed, using PubMed, Embase and GoogleScholar, combining the terms “appendix”, “appendicitis”, “stump”, “residual”, “recurrent” and “retained”. In total, 127 studies were included, descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
0
15
0
2
Order By: Relevance
“…One review found that most cases of remnant appendix cancer required further extensive surgery but this was largely attributed to a delayed diagnosis resulting in complications requiring more extensive surgery. 10 In summary, this represents an unusual presentation of a mucinous adenocarcinoma arising from the remnant appendix as a retroperitoneal cyst. It is important to not leave behind any appendix during appendicectomy and caution should be exercised when excising unidentified retroperitoneal lesions due to the risk of rupture and local spread.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…One review found that most cases of remnant appendix cancer required further extensive surgery but this was largely attributed to a delayed diagnosis resulting in complications requiring more extensive surgery. 10 In summary, this represents an unusual presentation of a mucinous adenocarcinoma arising from the remnant appendix as a retroperitoneal cyst. It is important to not leave behind any appendix during appendicectomy and caution should be exercised when excising unidentified retroperitoneal lesions due to the risk of rupture and local spread.…”
mentioning
confidence: 80%
“…The literature on appendiceal stump adenocarcinoma is limited and it is unclear whether a more aggressive surgical approach should be taken to management. One review found that most cases of remnant appendix cancer required further extensive surgery but this was largely attributed to a delayed diagnosis resulting in complications requiring more extensive surgery 10 …”
Section: Figurementioning
confidence: 99%
“…Surgical resection seems to be the treatment of choice in the reported cases. The choice of either laparotomy or laparoscopy depends on various factors like the patient's clinical condition and the local expertise and resources [5,12]. A more extensive operation should generally not be required as long as the appendiceal stump can be readily identified and the cecum itself does not show evidence of a significant amount of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of laparotomy or laparoscopy depends on various factors such as the clinical condition of the patient and whether or not the diagnosis was made preoperatively. 5 , 12 If the appendix stump can be easily identified and the cecum is not significantly inflamed, more extensive surgery should not be indicated. Some authors describe a critical view of the appendix similar to the critical view of safety of cholecystectomy to decrease the rate of this complication.…”
Section: Discussionmentioning
confidence: 99%